Typology of Mosque Architecture in the Greater Bandung Area, Indonesia - Nurcahya, Yan; Hidayat, Asep Achmad; Supendi, Usman; Kusdiana, Ading; Gumilar, Setia; Hakim, Ajid (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This research focuses on the typology of mosques in the Bandung area, Indonesia. Due to its close ties to Islam, research on mosque typology is still limited. This mosque holds significant value within the Muslim community. This research was conducted in Greater Bandung: Bandung City, Cimahi City, Bandung Regency, West Bandung Regency, and Sumedang Regency. This study employed qualitative methods (Creswell, 2008) with descriptive research characteristics. Using the Bandung Grand Mosque as a reference, as suggested in previous studies, the results show that the dome-shaped roof element is a dominant feature replicated by mosques in Greater Bandung. Other elements, such as columns, openings, and roof ornamentation, are also replicated by several research subjects, but to a lesser extent. This research provides a broader overview of the area, with a more diverse analysis of factors such as time, socio-cultural, and technological aspects.